An Allegory of Conflict between Nationalism and Feudalism in Shaw’s Saint Joan - Neupane, Dipesh (Patan Prospective Journal, 2022)
This paper explores the significance of allegory of the conflict between the good and evil, between ignorance and knowledge, between religious faith and hypocrisy, between reason and superstition, between truth and falsehood in Shaw’s Saint Joan. Joan is the generous lady who comes into conflict with discipline and established authority. She is the saint, the Christ, who is martyred in every age and country so that truth and righteousness may live upon the earth. The conflict of Joan with established authority is a continuing conflict which has always been there. According to Shaw’s philosophy of creative evolution, Joan symbolizes the upward urge of the life Force. Her enemies stand for the various obstacles and hindrances that retard life’s upward movement. This paper attempts to show how Shaw employs his political allegory to represent the British imperialism and people’s mission and struggle to extricate it from the grip of British rulers. Saint Joan is a true figure to go against them, and thereby attained martyrdom in course of her struggle at the end. This paper conceptualizes the theoretical concept of colonial studies in which the oppressors come into the conflict with the oppressed in different ways. Joan as the oppressed go against the oppressors like Cauchon and The Earl of Warwick for the sake of freedom from imperialism cherishing nationalism.